Rapid diagnosis of TB using Aptamer-based assays for Mycobacterium tuberculosis antigens in children and adolescents - Rajesh Bethu; Hema Gupta Mittal; Tarun K Sharma; Anuradha Shulania; Neera Sharma; Shmitha Rangarajan; Prerna Jain (Lung India, 2023)
Background: Despite advances establishing microbiological evidence of tuberculosis (TB) is still a concern in children due to the limitation of availability of sample and predominance of extrapulmonary TB, there is unmet need for diagnostic tests which are low cost, rapid and sensitive and specific. Methods: This study evaluated the utility of aptamer-based assay for detecting mycobacterium tuberculosis antigens HspX and MPT 64 in rapid diagnosis of TB in children up to 18 years of age in a tertiary medical college. A total of 100 children were sequentially enrolled with presumptive pulmonary (n = 52 and extrapulmonary n = 48) TB based on clinico-radiological characteristics. The samples were evaluated with ALISA technique for TB antigens and compared with the results of ZN microscopy, GeneXpert and mycobacterial culture MGIT. Results: The enrolled children had mean age (11.7 + 4.4 years) with both pulmonary (n = 52) and extrapulmonary TB (n = 48). Our study results concluded poor results of smears (11% positivity, sensitivity: 17.7%, NPV: 42.7%) and better of GeneXpert (positivity: 42%, sensitivity of 67.4%, NPV: 65.5%) and culture (positivity 57%, sensitivity 91.9%, NPV 88.3%). HspX antigen by ALISA had comparable results (positivity: 49%, sensitivity: 62.9%; NPV: 54.9%). MPT 64 antigen by ALISA also had similar results (positivity: 45%, sensitivity: 58% and NPV 52, 3%). Sensitivity and specificity were higher in pulmonary TB compared to EPTB for both antigens. HspX antigen assay by ALISA and MPT 64 ALISA over existing microbiological diagnostic methods had additional of 13%. Conclusion: ALISA technique for mycobacterium antigens HspX and MPT 64 was rapid, low-cost test (1-3$/test) high sensitivity and specificity and comparable to currently available methods.